RENCANA PENGELOLAAN GREEN BUILDING DENGAN PENDEKATAN BUILDING ENVIRONMENT MANAGEMENT (BEM) - Regina Regina; Liong Ju Tjung; Priyendiswara A.B. Priyendiswara (Jurusan Arsitektur dan Perencanaan, 2019)
The concept of green building is now increasingly being applied in Indonesia, especially DKI Jakarta due to the increasing prevalence of global warming. Adapting to climate change and the increasing number of tall buildings in Indonesia, the GBCI (Green Building Council Indonesia) concluded that the biggest cause of energy use was due to the use of the building sector of around 48%, while the other 27% was in the transportation sector, then 25% in the industrial sector. GBCI applies certification in the form of